The Effect of Pseudofrazil Particle Entrainment on Salinity Measurements. Issue 1 (11th January 2023) - Richter, Maren Elisabeth; Smith, Inga J.; Everts, Jonathan R.; Russell, Peter; Langhorne, Pat J.; Leonard, Greg H.
Abstract: Salinity effects of particles entrained into conductivity cells have previously mainly been studied in the context of suspended sediment. Particles influencing conductivity cells can also be small ice crystals (frazil) that may form in supercooled water. The detection of supercooled water depends on accurate, high precision temperature, salinity and pressure measurements. As it is currently not possible to measure salinity in situ, the standard procedure is to measure conductance over a known volume and calculate salinity. Frazil ice entrained into a conductivity cell changes the volume of conductive fluid in the conductivity cell, thus changing the conductivity, salinity and supercooling measurements. We present results on the effect of entraining microplastic into a Sea‐Bird Electronics conductivity cell to simulate the effect of frazil. We show that particle volumes comparable to frazil volumes observed in the ocean change the measured conductivity and led to changes in calculated supercooling between 0.3 and 10 mK, possibly up to the same order of magnitude as naturally observed supercooling in the ocean. Further, we demonstrate that where supercooling is present, natural frazil ice concentrations can have an appreciable effect on parameters calculated with both the Equation of State of Seawater 1980 and Thermodynamic Equation of Seawater 2010 equations of state of seawater. Thus, to ensure accurate measurements in locations of very high frazil concentration, the entrainment of frazil needs to be prevented, which is not possible with methods currently available, or corrected for. An example for such a correction is given and could be modified to be applicable to other particles, for example, sediment. Plain Language Summary: Supercooling in the ocean (water colder than its freezing point but still liquid) has wide‐ranging impacts on heat and salt transport, both in the water and in neighboring ice shelves and sea ice. However, oceanographic instruments currently in use are not designed to measure supercooling. Small ice crystals called frazil ice, which may form in supercooled water, led to falsely low salinity measurements which leads to falsely high levels of supercooling being recorded. Here we present a study that quantifies the salinity effect of frazil ice in seawater by studying the effect of plastic particles with similar material properties as frazil ice. We present measurements and calculations which can be used to correct for this effect in certain novel instruments or where frazil/particle concentration and conductivity is known. This research is of interest not only for oceanographers working in high latitude oceans but also for those working in waters with suspended matter such as sediments in estuaries and requiring highly accurate salinity values. To facilitate this, we compare our results to previously published studies of the effect of sediment–water mixtures flushed into conductivity cells. Key Points: Pseudofrazil particles influence conductivity measurements and are a good proxy for frazil ice High concentrations of frazil ice can cause falsely high supercooling measurements If frazil concentration is known, conductivity effects can be corrected for